Extracellular vesicles and their role in gestational diabetes mellitus. (15th September 2021) - James-Allan, Laura B.; Devaskar, Sherin U.
Abstract: Gestational diabetes mellitus (GDM) is a complex disorder that is defined by glucose intolerance with onset during pregnancy. The incidence of GDM is increasing worldwide. Pregnancies complicated with GDM have higher rates of maternal and fetal morbidity with short- and long-term consequences, including increased rates of cardiovascular disease and type II diabetes for both the mother and offspring. The pathophysiology of GDM still remains unclear and there has been interest in the role of small extracellular vesicles (sEVs) in the maternal metabolic adaptations that occur in pregnancy and GDM. Small EVs are nanosized particles that contain bioactive content, including miRNAs and proteins, which are released by cells to provide cell-to-cell communication. Pregnancy induces an increase in total and placental-secreted sEVs across gestation, with a further increase in sEV number and changes in the protein and miRNA composition of these sEVs in GDM. Research has suggested that these sEVs have an impact on maternal adaptations during pregnancy, including targeting the pancreas, skeletal muscle and adipose tissue. Consequently, this review will focus on the differences in total and placental sEVs in GDM compared to normal pregnancy, the role of sEVs in the pathophysiology of GDM and their clinical application as potential GDM biomarkers. Highlights: The incidence of GDM is increasing which, leads to increaed risk of short- and long-term complications for the mother and offspring. Extracellular vesicles (EVs) are nanosized particles with a bioactive content with a role in cell-to-cell communication. The concentration and bioactivity of EVs is altered in GDM pregnancies. Proteins and miRNAs encapsulated in circulating EVs are dysregulated in GDM pregnancies. In GDM circulating EVs, secreted from the placenta and non-placental sources, induce changes in maternal physiology.